Reproductive biology of Gattan females Barbus xanthopterus (Heckel, 1843) used for artificial breeding in Fish Hatchery of Marine Science Center - AI-Lamy, Jinan Hassan; AI zaidi, Faleh Mousa; AI-Mudhaffar, Raja Abd Ali; Awfi, Layla Abboud (Iraqi Journal of Aquaculture, 2022)
Some aspects of reproductive biology of Gattan Barbus xanthopterus females were studied from 15-30 March, 2009. These fishes were coughed from Huweiza Marsh, Southern Iraq and from Therthar Reservoir, Western Iraq, and used for artificial breeding in Marine Science Center Hatchery. Total lengths ranged between 550-806 mm, total weights ranged between 3100-7250 g, and their age ranged from 3-6 years. It had been found that all examined ovaries were in ripe stage that means females cached from Huweiza Marsh were ready for artificial breeding and possess suitable (3.64- 11.03) gonado somatic index (GSI), while females collected from Therthar Reservoir had low GSI (1.15-1.33). Average of eggs diameters was 1.56 mm for fish of 550 mm total length and 3400 g, while it was 2.09 mm for fish of 802 mm total length and 7005 g. However, generally there was positive relationship between total lengths and eggs diameters with no significant correlation (r = o.47, P<0.01). Absolute fecundity for Gattan was ranged between 1494191-518650 eggs, and relative fecundity was between 85.8-286.2 egg/g, while there was low positive relation between absolute fecundity and total fish weight with no significant correlation (r= 0.33, P<0.01).